Investigation of periodic modes in nonlinear systems with fractional order integrator - Kavuran, Gurkan; Yero?lu, Celaleddin (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper investigates the effect of fractional order integrator on the nonlinear feedback systems. The effect of fractional order integrator, which is proposed to place in front of relay with dead zone on the second order system, is analysed comparatively using Describing Function method and simulation results. Since the proposed approach provides the opportunity for the selection of a wide phase range, it can be considered as an effective method to select relevant sampling frequency and to investigate limit cycles in modulators and demodulators that are used for signal conversion applications. © 2015 IEEE.
Do?rusal Olmayan Kesir Dereceli Integratörlü Sistemlerde Periyodik Kiplerin Incelenmesi
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: Describing function; fractional order integrator; limit cycles; sigma-delta modulation